2015
DOI: 10.1371/journal.pone.0140653
|View full text |Cite
|
Sign up to set email alerts
|

Paliurus Fruits from the Oligocene of South China and Their Phytogeographic Implications

Abstract: Paliurus favonii Unger is recognized and described based on fruits from the Oligocene Ningming flora of Guangxi, South China. Characteristics of the present specimens include circular winged fruits that are 10.0–11.5 mm in diameter with a central endocarp at 3.0 to 4.0 mm in diameter. The specimens fall into the morphological range of the fossil species P. favonii, which has been observed in other Cenozoic sites in the Northern Hemisphere. The present discovery represents the lowest latitude distribution of P.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…It should be noted that several recent studies have suggested that long-distance dispersal may have played important roles in certain intercontinental disjunctions (Nie & al., 2005;Popp & al., 2011). Furthermore, long-distance dispersal could potentially have caused the disjunct distribution of Paliurus, because the species' winged drupes may be dispersed by wind (Dong & al., 2015). However, long-distance dispersal need not be highly correlated with the morphology of diaspores (Higgins & al., 2003;Thomas & al., 2015).…”
Section: Version Of Recordmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted that several recent studies have suggested that long-distance dispersal may have played important roles in certain intercontinental disjunctions (Nie & al., 2005;Popp & al., 2011). Furthermore, long-distance dispersal could potentially have caused the disjunct distribution of Paliurus, because the species' winged drupes may be dispersed by wind (Dong & al., 2015). However, long-distance dispersal need not be highly correlated with the morphology of diaspores (Higgins & al., 2003;Thomas & al., 2015).…”
Section: Version Of Recordmentioning
confidence: 99%
“…Furthermore, the dispersal distance of diaspores is limited by the height of plants ( Thomson & al., 2011). As species of Paliurus are shrubs and small trees, long-distance dispersal of the genus by this mechanism seems unlikely (Dong & al., 2015). Thus, vicariant fragmentation driven by uplift of the QTP seems the likeliest explanation of the present disjunction.…”
Section: Version Of Recordmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the incompleteness of the fossil record of diaspores and historical sampling bias towards mid‐latitude regions, databases of previous studies that looked at diaspore size through time were limited by their geographical extent, and by the absence of more recent fossil discoveries from low‐latitude palaeofloras, e.g. floras from the Paleocene of South America and Oligocene of South China (Doria et al ., 2008; Wing et al ., 2009; Chen & Manchester, 2015; Dong et al ., 2015; Chen et al ., 2017 b ; Liufu, Chen & Wang, 2017; Hu et al ., 2017). We present a new data set including more than 800 georeferenced occurrences of fossil diaspores to quantify patterns of fleshy diaspore size and abundance through time, at both low and mid‐ to high palaeolatitudes.…”
Section: Introductionmentioning
confidence: 99%